Effect of sintering temperature on mechanical and microstructural properties of bovine hydroxyapatite (BHA) - OKTAR, FAİK NÜZHET (SPRINGER, 2006)
The influence of sintering temperature on densification, microstructure and the mechanical properties of bovine hydroxyapatite (BHA), produced by a calcination method, was investigated. Densification and mechanical properties improved with increasing sintering temperature in the range between 1000 degrees C and 1300 degrees C, with optimum properties being obtained at a sintering temperature of 1200 degrees C. The measured mechanical properties indicate that sintered BHA bodies are interesting biomaterials for further investigation in biomedical applications.
Keywords: bovine hydroxyapatite; sintering; mechanical properties; microstructure; REINFORCED HYDROXYAPATITE; BONE; COATINGS; DENTIN